Efektifitas Digitalisasi Penghimpunan Dana Zakat pada Badan Amil Zakat Nasional (BAZNAS) Kota Tangerang - Nur Jamaludin; Siti Aminah (Universitas Islam Negeri Sunan Ampel Sunan Ampel, 2021)
In the era of digitalization technology, the Zakat collection Boards need to enhance their ways to optimalize the fund rising. BAZNAS of Tangerang City adapts their capacity through implement the digitalization of fundrising by suing SIMBA (Information Management System of BAznas). The BAZNAS digitalization system in Tangerang City divided into 2 parts, namely internal and external including SIMBA and digital zakat. This study uses a qualitative analysis method with data collection techniques through observation, in-depth interviews, and documentation. Informants selected in this research is determined using purposive sampling technique. Research result shows that the digitization of zakat fund collection in BAZNAS in Tangerang City the implementation has been effective. However, there are still some obstacles faced by BAZNAS staff officers and BAZNAS muzaki such as internet network problems and reporting proof of payment of zakat. Another finding, the implication in this research is BAZNAS Kota Tangerang needs to evaluate human errors that occur in digital systems and strengthen them security and keep innovating.